First Confirmed Record of the Rare Great Evening Brown, Melanitis zitenius zitenius (Herbst, 1796) (Lepidoptera: Nymphalidae: Satyrinae) in the Garhwal Himalaya, Uttarakhand, India - Singh, Arun Pratap (Indian Forester, 2025)
No Abstract.